2014
DOI: 10.1186/2049-1891-5-42
|View full text |Cite
|
Sign up to set email alerts
|

Preslaughter diet management in sheep and goats: effects on physiological responses and microbial loads on skin and carcass

Abstract: Sixteen crossbred buck goats (Kiko x Spanish; BW = 32.8 kg) and wether sheep (Dorset x Suffolk; BW = 39.9 kg) were used to determine the effect of preslaughter diet and feed deprivation time (FDT) on physiological responses and microbial loads on skin and carcasses. Experimental animals were fed either a concentrate (CD) or a hay diet (HD) for 4 d and then deprived of feed for either 12-h or 24-h before slaughter. Blood samples were collected for plasma cortisol and blood metabolite analyses. Longisimus muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
6
1
Order By: Relevance
“…In general, plasma concentrations of cortisol are reported to change when animals are subjected to stressors3. Previous studies have shown that pre-slaughter factors, such as the feeding system and fasting period, also negatively affect meat quality by increasing serum cortisol levels4. In addition, other studies suggested that when pigs were transported during the cold season, there were higher levels of cortisol and a greater quantity of tough meat5.…”
mentioning
confidence: 99%
“…In general, plasma concentrations of cortisol are reported to change when animals are subjected to stressors3. Previous studies have shown that pre-slaughter factors, such as the feeding system and fasting period, also negatively affect meat quality by increasing serum cortisol levels4. In addition, other studies suggested that when pigs were transported during the cold season, there were higher levels of cortisol and a greater quantity of tough meat5.…”
mentioning
confidence: 99%
“…Gutta et al [13] reported that feed deprivation for 24 h increased E. coli, total coliform counts, and Enterobacteriaceae counts in the rumen of Kiko × Spanish goats and Dorset × Suffolk sheep, compared with 12 h deprivation and with no significant change in the pH of rumen liquor. However, no difference in E. coli or total coliform counts were observed on sheep and goat (Kiko × Spanish) carcasses as a result of feed deprivation time [11]. In contrast, experimentally infected adult sheep showed no increase in fecal shedding of E. coli O157:H7 during feed withdrawal [48].…”
Section: Feed Withdrawal and E Coli Populationsmentioning
confidence: 93%
“…Preharvest meat goat management, slaughter and processing, and postharvest carcass and meat handling methods vary among different countries and regions. The E. coli counts on goat skin prior to slaughter generally range from 2.2 to 2.5 log 10 CFU cm −2, and those on carcasses before washing range from 2.1 to 2.3 log10 CFU cm −2 [10,11]. It is not clear to what extent factors such as sex, age, and breed can influence E. coli shedding in goats.…”
Section: Prevalence Of E Coli In Goatsmentioning
confidence: 99%
See 2 more Smart Citations